Pakistan's Macroeconomic Adjustment and Resumption of Growth, 1999-2004. (IMF Working Papers; Working Paper ;, 2005)
The main findings are as follows: (1) an increase in private national saving during 2001-03 was the key contributor to the turnaround in Pakistan's external current account during this period; (2) while Pakistan's growth was mainly export-led before 2003-04, it was largely led by domestic demand in 2004, especially consumer demand but also private and public investment; and (3) the structural reforms implemented in Pakistan during the past four years should make the observed strengthening in domestic savings and rise in domestic investment permanent, auguring well for accelerated growth within a sustainable external balance. The country's growth prospects would be further enhanced by a more externally driven growth process, and by an acceleration of structural reforms to further improve productivity and the investment climate.